Pengaruh Olahraga Aerobik Tipe Closed Skill Terhadap Konsentrasi Mahasiswa Kedokteran Universitas Airlangga - Dzulqarnain Andira; Raden Argarini; Margarita Maria Maramis (UIR Press, 2019)
This research was conducted to determine the effect of using aerobic of closed-skill type toward students’ concentration of Pediatric Department of Universitas Airlangga. This research was experimental design which randomized pre-test post-test control group with 36 students who seldom doing sport as samples. These students were divided into two groups; experimental group and control group. Experimental group did aerobic with closed technique type training which medium to high intensity around 75 minutes a week for 3 weeks. On the otherwise, control group did not do it. The research instruments were xbox with kinetic sensor and attention network test. The students’ concentration was measured three aspects such as alerting, orienting and conflict effect. This analysis technique was done by using statistical technique through SPSS. The result shown that there was no significant different between experimental group and control group by comparing average score of pre-test and post-test for alerting aspect (0.895), orienting (0.572), and conflict effect (0.019). Therefore, there was significant different from pre-test and post-test of control group for conflict effect (0.019) but there were not significant different for alerting (0.072) and orienting (0.735) and for experimental group, there was significant different in alerting (0.02) and conflict (0.001) but there was not significant different for orienting effect (0.653). It can be concluded that there was not significant effect on students’ concentration between control group (0.778) and experimental group (0.571). It means that aerobic cannot influence students’ concentration.